Subgingival Microbiota in White Patients With Desquamative Gingivitis: A Cross‐Sectional Study. Issue 7 (1st July 2017) - Arduino, Paolo G.; Romano, Federica; Sasia, Danilo; Broccoletti, Roberto; Ricceri, Fulvio; Barbui, Anna Maria; Brossa, Silvia; Cipriani, Raffaella; Cricenti, Luca; Cabras, Marco; Aimetti, Mario
Abstract : Background: Presence of epithelial desquamation, erythema, and erosions on gingival tissue is usually described in the literature as desquamative gingivitis (DG). A wide range of autoimmune/dermatologic disorders can manifest as DG, although the two more common are oral lichen planus and mucous membrane pemphigoid. The aim of this study is to investigate prevalence of 11 periodontopathogenic microorganisms in patients with DG and to compare it with the microbiologic status of individuals affected by plaque‐induced gingivitis (pGI). Methods: Cross‐sectional clinical and microbiologic data were obtained from 66 patients (33 in each group). Subgingival plaque samples were analyzed using semiquantitative polymerase chain reaction analysis. Results: Statistically significant difference, but with little clinical significance, was observed in gingival conditions between the two groups, probably due to the worse home control hygiene of patients with DG. Prevalence and levels of Aggregatibacter actinomycetemcomitans, Eikenella corrodens, and Fusobacterium nucleatum/periodonticum were statistically higher in samples from patients with DG than in those with pGI. In multivariate regression models, subgingival colonization of A. actinomycetemcomitans and F. nucleatum/periodonticum was not statistically associated with DG, whereas, high levels of E. corrodens were associated with 13‐fold increased odds for DG. Conclusions: Microbiologic differences were found in subgingival plaque for patients with DG and pGI. This may suggest possible association between periodontal pathogens and DG.